2021
DOI: 10.7759/cureus.17550
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Coronary Artery Disease and Left Ventricular Hypertrophy

Abstract: Ischemic heart disease (IHD) is the leading cause of death worldwide, and it is defined as an imbalance between myocardial oxygen supply and demand. Coronary artery disease (CAD) and left ventricular hypertrophy (LVH) are two common causes of IHD that independently result in myocardial ischemia. CAD decreases myocardial blood and oxygen supply whereas LVH increases myocardial oxygen demand. The coexistence of both CAD and LVH results in a significant increase in oxygen demand while simultaneously lowering oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 65 publications
0
8
0
2
Order By: Relevance
“…However, in cases of severe hypertrophy, this increase in size is not proportional and can result in an increase in cardiac demand, potentially leading to ischemia. [11][12][13] In these cases, the underlying mechanisms leading to the increase in coronary artery size may involve enhanced chronic stimulation of endothelium-derived relaxing factor perfusion pressure, circulating neurohormones, and local growth factors. 12 In our patient, diffuse dilatation of the coronary arteries without stenosis was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in cases of severe hypertrophy, this increase in size is not proportional and can result in an increase in cardiac demand, potentially leading to ischemia. [11][12][13] In these cases, the underlying mechanisms leading to the increase in coronary artery size may involve enhanced chronic stimulation of endothelium-derived relaxing factor perfusion pressure, circulating neurohormones, and local growth factors. 12 In our patient, diffuse dilatation of the coronary arteries without stenosis was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that in cases of mild to moderate left ventricular hypertrophy, there is a proportional increase in the size of the coronary vessels. However, in cases of severe hypertrophy, this increase in size is not proportional and can result in an increase in cardiac demand, potentially leading to ischemia 11–13 . In these cases, the underlying mechanisms leading to the increase in coronary artery size may involve enhanced chronic stimulation of endothelium‐derived relaxing factor perfusion pressure, circulating neurohormones, and local growth factors 12 …”
Section: Discussionmentioning
confidence: 99%
“…LVH can, independently of CAD, result in myocardial ischemia, which can further increase morbidity and mortality due to myocardial infarction. 59 This is supported by the fact that the gain-of-function variant, p.Gly23Val, identified in patients with Noonan syndrome is accompanied by cardiac hypertrophy and a 40-fold F I G U R E 3 Muscle rat sarcoma virus (MRAS) and associated traits. MRAS variants are associated with a variety of common genetic conditions, including coronary artery disease, Noonan syndrome, or cardiac hypertrophy.…”
Section: Mras Risk Variants For Atherosclerosis Cad and Strokementioning
confidence: 98%
“…CHD, especially MI, leads to CM damage or death due to ischemia and hypoxia, resulting in a localized cardiac function deficit. Under prolonged stimulation, peripheral CMs gradually hypertrophy to compensate for partial cardiac function [ 110 , 111 ]. The early stage of MH is a beneficial compensatory response for the organism, but its compensatory capacity is limited.…”
Section: Ferroptosis Involvement In the Pathological Progression Of Chdmentioning
confidence: 99%